In Vitro Bacterial Leakage at the Implant-Abutment Connection of Two Dental Implant Systems with Internal Connection - Azadeh Khajavi; Shabnam Mohseni; Amir Peymani; Mehrak Amjadi (Tehran University of Medical Sciences, 2020)
Objectives: Bacterial leakage at the implant-abutment interface is one of the main causes of peri-implant inflammation. One of the factors that influences bacterial leakage is the structural design of the interface. Considering the limited studies that have examined slip-joint connections, a comparative study of bacterial leakage was performed on two different systems namely Zimmer (Tapered Screw-Vent, Zimmer Dental) with slip-joint connection and Argon (Konus K3pro, Argon Implants) with conical connection. Materials and Methods: Twenty-two implants were selected in 2 groups (11 Zimmer with slip-joint connection, and 11 Argon with conical connection) with similar platforms. Escherichia coli (E. coli) suspension (2 μL) was pipetted into the internal lumen of implants. The abutments were screwed onto the implants with a closing torque of 30 Ncm. The assemblies were placed in culture broth for 6, 24, 48 and 72 h, and 7 and 14 days. The colonies were counted and analyzed by the Mann-Whitney test (a=0.05). Results: Microleakage was observed in 20% of the samples of conical connection group after 6 h to 2 days, and in 50% of the samples in slip-joint connection group after 3 to 7 days. There was a significant difference in bacterial leakage rate between the two implant groups (P<0.001) but no significant difference was seen in bacterial leakage over time (P>0.05). Conclusion: Type of connection had a significant effect on bacterial leakage, but the rate of bacterial leakage did not significantly change over time.